The in vitro Mycobacterium bovis BCG Moreau infection of human monocytes that induces Caspase-1 expression, release and dependent cell death is mostly reliant upon cell integrity - Paulo R. Z. Antas; Carlos G. G. Ponte; Matheus R. Almeida; Lawrence H. P. Albuquerque; Periela S. Sousa-Vasconcelos; Thaíze Pedro; Natália L. S. Gomes; Otacílio C. Moreira; Fernanda C. Silva; Luíz R. R. Castello-Branco; Rosa T. Pinho (BMC, 2019)
Abstract Background Caused by Mycobacterium tuberculosis, tuberculosis (TB) is an extremely contagious disease predominantly affecting the lungs. TB is found worldwide and has a major impact on public health safety primarily due to its high mortality rate. Applied for over a hundred years as a preventive measure, Mycobacterium bovis BCG remains the only available TB vaccine. Only one seminal study about the apoptotic pathways induced by this vaccine in the monocytic lineage of the host cell has found the effects of BCG on regulation of apoptosis. The aim of this study was to explore beyond that pioneer study the pathway related to the in vitro cell-death pattern and the inflammatory response to the BCG vaccine in human monocytes. Methods Cohorts of HIV-negative volunteers were enrolled: adult Healthy Donors (HD) and neonates' Umbilical Cord Blood (UCB) individuals. Host mononuclear cells were infected with the M. bovis Moreau strain of BCG vaccine at 16, 24, 48, and 72 h. The Real-Time RT-PCR for TRADD, Bcl-2, and Caspases-1 and -3 were performed, and supernatants were assayed in parallel for Caspase-1, NLRP3, HO-1, and IL-1β levels whereas caspases were assessed intracellularly. The effect of a BCG infection in monocytes was characterized via a metabolic activity assay by LDH release profiles. Results Overall, the BCG vaccine induced significantly higher Caspase-1 and Bcl-2 mRNA levels in both the HD and UCB groups (p-value ≤0.05). In addition, a significant increase solely in Caspase-1 protein levels was also noted in both HD and UCB (p-value ≤0.05) notwithstanding the absence of any damaged cell membranes. Conclusions Our data directly corroborate other findings showing that BCG Moreau led to an increased secretion of IL-1β but not IL-18, two Caspase-1-activated cytokines, and are also in support of the model that the BCG Moreau infection of human mononuclear cells may induce a cell-death pattern involving Caspase-1 activation.